PPAR-γ agonists inhibit TGF-β1-induced chemokine expression in human tubular epithelial cells - Wang Wei-ming; Zhang Hui-di; Jin Yuan-meng; Zhu Bing-bing; Chen Nan (Acta Pharmacologica Sinica, 2016)
Aim: Peroxisome proliferator-activated receptor-γ (PPAR-γ) has a wide range of biological functions, including anti-inflammation. In this study, we investigated the inhibitory effects of PPAR-γ on transforming growth factor β1 (TGF-β1)-induced interleukin-8 (IL-8) and monocyte chemoattractant protein-1 (MCP-1) expression in renal tubular epithelial cells (HK-2). Methods: HK-2 cells were pretreated with 15d-PGJ2 or troglitazone (TGL) and then treated with TGF-β1. Expression of MCP-1 and IL-8 was measured using real-time PCR and ELISA. Results: Treatment with 5 ng/mL TGF-β1 for 24 h increased both MCP-1 and IL-8 mRNA and protein levels in HK-2 cells. Both 15d-PGJ2 at 2.5 and 5 μmol/L and TGL at 2.5 μmol/L exhibited inhibitory effects on TGF-β1-induced MCP-1 expression. Additionally, 15d-PGJ2 at 2.5 and 5 μmol/L and TGL at 2.5 μmol/L inhibited TGF-β1-induced expression of IL-8. Conclusion: PPAR-γ agonists (15d-PGJ2 and TGL) could inhibit the TGF-β1-induced expression of chemokines in HK-2 cells. Our results suggest that PPAR-γ agonists have the potential to be used as a treatment regimen to reduce inflammation in renal tubulointerstitial disease.